Salinity and drought, a comparison of their effects on the relationship between yield and evapotranspiration - Katerji N.; van Hoorn I.W.; Hamdy A.; Mastrorilli M.; Karam F. (Mediterranean crop responses to water and soil salinity: Eco-physiological and agronomic analyses, 2002)
The observations of a long-term experiment on the use of saline water were used to check the hypothesis whether models developed for drought conditions are valid for yield prediction in case of salinity. The models for the relation between yield and evapotranspiration, proposed by Stewart and Hagan (1973) and Stewart et al. (1977), were used for maize, sunflower, potatoes and soybean. The yield estimation for maize, and sunflower was quite accurate, for potatoes somewhat less, but unsatisfactory for soybean. The estimated yield of soybean under saline conditions was higher than the measured one. This may be attributed to the differences in salt tolerance between soybean varieties or to an additional effect of salinity on the nitrogen supply of this legume.